Additions to the global diversity of Cladonia. (27th September 2016) - AHTI, Teuvo; PINO-BODAS, Raquel; FLAKUS, Adam; STENROOS, Soili
Abstract: In our ongoing study of the genus Cladonia, we have encountered several specimens that have proved to represent undescribed species. Four of them are described here as new. Cladonia camerunensis (Cameroon) resembles C. didyma (Fée) Vain., but the former has a coarsely granular surface and a melanotic podetial base; C. compressa (Bolivia) is distinguished by a dominant primary thallus and deeply divided and phyllopodiate podetia; C. longisquama (Seychelles) has well-developed squamules and contains barbatic acid; C. vescula (Bolivia, Peru) differs from C. peziziformis (With.) J. Laundon by an ecorticate podetial surface and the production of homosekikaic acid. The names C. aspera Ahti & Kashiw. and C. crinita (Delise ex Pers.) Ahti are shown to be illegitimate later homonyms and are replaced by the names C. asperula and C. perfoliata, respectively. The neglected name C. botryoides (Tuck.) Vain. is shown to be a synonym of C. squamosa. Another overlooked name, C. crinita Bertol., is shown to be the earliest name for C. evansii, but we propose to retain the latter through conservation. The typification of C. beaumontii Tuck. is amended. Cladonia conspicua is reinstated on the basis of new data. New range extensions in Canada and the United States are given for the poorly documented species C. oricola.